PENGARUH PROFITABILITAS, BIAYA OPERASIONAL, DAN MANAJEMEN LABA TERHADAP PAJAK PENGHASILAN BADAN PADA PERUSAHAAN MANUFAKTUR SEKTOR KONSUMSI DI BEI (Periode 2017-2020) - Novita Ayudiya Anggraeni; Abubakar Arief (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
Taxes are the largest contributor to state revenue in Indonesia. Corporate income tax is part of the tax that has a large contribution to the amount of tax revenue. This study aims to test and provide empirical evidence of the effect of profitability, operating costs, and earnings management on corporate income tax. The type of data used in this study is secondary data derived from the financial statements of consumer goods sector companies listed on the Indonesia Stock Exchange for the period 2017 to 2020. The sampling method is a purposive sampling method with a total of 156 observational data. The analytical method used in this study is multiple linear regression analysis with SPSS version 25 analysis tool. The results showed that profitability and operating expense had a positive effect on corporate income tax, while earnings management had no effect on corporate income tax.